Exigency-based real-time scheduling policy to provide absolute QoS for web services - Casagrande, Lucas S.; Mello, Rodrigo F. de; Bertagna, Ricardo; Andrade Filho, Jose A.; Monaco, Francisco J. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2007: Anais do XIX International Symposium on Computer Architecture and High Performance Computing, 2007)
Telemedicine, distance learning and e-commerce applications impose time constraints directly related to the efficacy of their operations. In order to offer reliability levels capable of meeting such requirements, mechanisms to provide QoS have been widely employed, what motivates this work to propose, implement and validate a real-time scheduling policy for providing absolute QoS for web services. The policy, named Exigency-Based Scheduling (EBS), intends to fast serve the most urgent requests, without degrading the whole system service. The current approach is based on the real-time scheduling, low latency and feedback scheduling, allowing a balanced configuration by the quantification of the exigency imposed to the system by the service classes. The technique evaluation uses metrics proposed in the present work. Experimental results confirm improvements in terms of QoS and client satisfaction.